Growth Performance and Hemato-Biochemical Profile in Broiler Chicken Supplemented on Shatavari (Asparagus racemosus) Root Powder and Vitamin E during Summer Season - Kant, Shashi; Ali, Nazim; Chandra, Gulab (Indian Journal of Animal Nutrition, 2018)
The effect of shatavari (Asparagus racemosus) and vitamin E supplementation on broiler performance, haematological and biochemical profile in summer season was studied during a 42 days experiment. One hundred twenty, day old broiler chicks were randomly allotted to 6 groups. Shatavari powder and vitamin E was added to the basal diet @ 0 and 0, 1 and 0, 1.5 and 0, 0 and 200, 1 and 200, 1.5% and 200 mg/ kg feed in treatments T1, T2, T3, T4, T5, and T6, respectively. Feed consumption was similar in all the groups. Body weight gain was higher (P<0.05) in the treatment groups as compared to control group, however, FCR was similar in all the groups. The values of mean corpuscular volume, mean corpuscular haemoglobin and mean corpuscular haemoglobin concentration, blood urea nitrogen and creatinine were lower (P<0.05) while those oftotal erythrocyte count, haemoglobin, packed cell volume, total serum protein, albumin and globulin levels were higher (P<0.05) in treatment groups in comparison to control group. A better response was found in terms of growth and haematological parameters in treatment with combination of 1.5% shatavari root powder and 200 mg/kg feed vitamin E.